Hubungan Emotional Intelligence dengan Learning Outcomes Pendidikan Kesetaraan Paket A - sofiyyah Salma; Yatim Riyanto (J+PLUS UNESA, 2026)
This study aims to determine the relationship between emotional intelligence and the learning outcomes of students in the Package A Equivalency Education program at PKBM Budi Utama in Surabaya. This study employs a quantitative approach with a correlational design. The study population consisted of 86 students, comprising 46 students as the research sample and 40 others used for instrument validation. Data collection was using a Likert scale questionnaire to measure students’ emotional intelligence, while academic achievement data was obtained through documentation study of students’ grades. Data analysis utilized the Pearson Product-Moment correlation test with the aid of SPSS. The research hypothesis posited a positive relationship between emotional intelligence and the learning outcomes of students in the Equivalency Education Program Package A. The results of the hypothesis test revealed a correlation coefficient of 0.676 with a significance level of 0.000, leading to the acceptance of Ha and the rejection of the H0. The strength of the relationship falls into the strong category, indicating that an increase in emotional intelligence tends to be followed by improvement in students’ learning outcomes. This study concludes that emotional intelligence has a significant relationship with the learning outcomes of students in the Equivalency Education Package A program at PKBM Budi Utama in Surabaya.